Concerns about composite reference standards in diagnostic research. (18th January 2018) - Dendukuri, Nandini; Schiller, Ian; de Groot, Joris; Libman, Michael; Moons, Karel; Reitsma, Johannes; van Smeden, Maarten
Abstract : Composite reference standards are used to evaluate the accuracy of a new test in the absence of a perfect reference test. A composite reference standard defines a fixed, transparent rule to classify subjects into disease positive and disease negative groups based on existing imperfect tests. The accuracy of the composite reference standard itself has received limited attention. We show that increasing the number of tests used to define a composite reference standard can worsen its accuracy, leading to underestimation or overestimation of the new test's accuracy. Further, estimates based on composite reference standards vary with disease prevalence, indicating that they may not be comparable across studies. These problems can be attributed to the fact that composite reference standards make a simplistic classification and then ignore the uncertainty in this classification. Latent class models that adjust for the accuracy of the different imperfect tests and the dependence between them should be pursued to make better use of data